Ovarian Small Cell Carcinoma of Pulmonary Type Arising in Mature Cystic Teratomas With Metastases to the Contralateral Ovary. (August 2015) - Rubio, Alejandro; Schuldt, Maolly; Chamorro, Clara; Crespo-Lora, Vicente; Nogales, Francisco F
A bilateral small cell ovarian carcinoma pulmonary-type (SCCOPT), arising in bilateral mature cystic teratomas (MCTs) presented as stage IIIB in a 37-year-old woman. Microscopically, tumor nests were related to the dermoid protuberance and expressed pancytokeratin, EMA, CD56, chromogranin A, NSE, synaptophysin, and SOX2. SALL4 was also focally positive. CDX2, TTF1, PAX8, CK7, CK20, and several neuroendocrine gut hormones were negative. Serum NSE was elevated. This case represents a SCCOPT arising in an MCT in the right ovary with metastasis to the left one also containing a synchronous MCT. Surface implants and lymphovascular invasion suggested metastasis from the right ovarian SCCOPT and excluded a metastatic origin from usual locations of small cell carcinoma (SCC). SCCOPT is morphologically identical to SCC elsewhere, even sharing NSE serum elevation. Although the tumor was closely related to teratomatous mature tissues, a complex immunohistochemical panel failed to provide a tissue of origin.